Modified Periosteal Inhibition (MPI) Technique for Immediate Implants: A Multi-Center Retrospective Case Series Study - Andrea Grassi; Lucia Memè; Roberto Rossi; Fabio Faustini; Fabio Marinotti; Fabrizio Bambini; Stefano Mummolo (Applied Sciences, 2023)
Background: Alveolar socket preservation is a topic of serious interest, and researchers have investigated this problem quite extensively. In terms of aesthetics, it is very important to avoid bone resorption if the clinician decides to insert the implant immediately after the extraction. Recently, a new approach utilizing a barrier external to the socket has been developed, which has advanced the evolution of this technique. Immediate implants have also created some difficulty when re-evaluated in long-term follow-up, especially when an aesthetic result is part of the goal of the procedure. Methods: The modified periosteal inhibition (MPI) technique, which has shown interesting outcomes, is evaluated in this paper on a large group of patients. In this case series, among 14 patients, 11 received immediate implants using the MPI technique and immediate provisionalization, and 3 received immediate implants using the MPI technique and customized healing abutment. All patients showed ridge preservation to different degrees, ranging from 0.02 to 1.17 mm, with an average gain of 0.51 mm. Results: all of the 14 patients maintained the original ridge shape, and 1 showed an increase in bucco-lingual size. Conclusions: This case series confirms the promising information reported in earlier studies on this technique. Larger samples will be necessary to confirm the predictability of this new approach.